Chapter Declinare la bioregione nei contesti urbani. Quartieri, reti di mutualismo e poli civici - CELLAMARE, Carlo (Territori, 2023)
The currently prevailing development model and its effects in terms of settlement organization have negative implications especially in metropolitan contexts, where the effects of large agglomerations, speculative dynamics and neoliberal exploitation are stronger. The idea of urban bioregion tries to build an alternative to the dominant, heteronomous model of settlement organization aiming at 'reterritorializing' the ecological question within the processes of production of space with an integrated and multidimensional approach, careful to enhance the capacities and possibilities of local self-government. It therefore also calls into question a rethinking of the forms of politics. The essay illustrates possible paths in this direction, starting from suburban neighbourhoods and put in place through mutualism networks and civic hubs, describing a few experimentations in the Roman area.